Safety and efficacy of lopinavir/ritonavir-containing antiretroviral therapy in patients aged <50 versus ≥50 years from randomized trials. (April 2014) - Fisher, Martin; Norton, Michael; Saget, Brad; Fredrick, Linda; Wyk, Jean van
ABSTRACT: : Aim: Data describing the safety and efficacy of antiretroviral therapy (ART) in HIV-infected patients aged ≥50 years are limited. We evaluated the effect of age on safety, efficacy and tolerability in patients aged <50 and ≥50 years receiving lopinavir/ritonavir (LPV/r)-containing ART.Methods: End points from AbbVie Inc. (IL, USA) or AIDS Clinical Trials Group randomized clinical trials in adults using LPV/r 800/200 mg/day as part of a three-drug regimen (follow-up ≥48 weeks) were evaluated using a random-effects meta-analysis (virologic efficacy; intent-to-treat; noncompleter = failure) or pooled data (other end points).Results: A total of 2608 patients (2294.3 patient-years of follow-up) from ten trials were included: 2248 patients (86.2%) <50 years of age and 360 (13.8%) ≥50 years of age. Demographics and baseline characteristics were similar between age groups. At week 48, 64.9 and 67.8% of patients <50 and ≥50 years, respectively, had plasma HIV-1 RNA <50 copies/ml (random effects meta-analysis p = 0.992). Mean change from baseline in CD4 + T-cell count was +193.9 and +163.5 cells/μl (<50 and ≥50 years, respectively; p < 0.001). Smaller proportions of patients <50 years of age discontinued due to adverse events (AEs)/HIV-related events (4.9 vs 9.4%; p = 0.001) and reported moderate-to-severe treatment-related AEs (30.5 vs 36.4%; p = 0.027) compared with patients ≥50 years of age.Conclusion: This analysis suggests LPV/r-anchored three-drug therapy in patients ≥50 years of age leads to comparable rates of virologic suppression, with a smaller increase in absolute CD4 + T cells and increased AEs, including discontinuations associated with AEs compared with patients <50 years of age.